Selective Detection of Cu+ Ions in Live Cells via Fluorescence Lifetime Imaging Microscopy - Priessner,M; Summers,PA; Lewis,BW; Sastre,M; Ying,L; Kuimova,MK; Vilar,R (Angewandte Chemie, 2021)
Abstract Copper is an essential trace element in living organisms with its levels and localisation being carefully managed by the cellular machinery. However, if misregulated, deficiency or excess of copper ions can lead to several diseases. Therefore, it is important to have reliable methods to detect, monitor and visualise this metal in cells. Herein we report a new optical probe based on BODIPY, which shows a switchon in its fluorescence intensity upon binding to copper(I), but not in the presence of high concentration of other physiologically relevant metal ions. More interestingly, binding to copper(I) leads to significant changes in the fluorescence lifetime of the new probe, which can be used to visualize copper(I) pools in lysosomes of live cells via fluorescence lifetime imaging microscopy (FLIM).